Office hysteroscopy: a review - Shanbhag, Vijayalakshmi; Bagde, Nilaj (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
With the invention of new techniques and modalities “see and treat” has become the norm of management now a days. Diagnostic hysteroscopy combined with histological examination of an endometrial biopsy is considered the ‘gold standard’ in the diagnosis of intrauterine abnormalities. The importance of office hysteroscopy lies in the fact that there is no need of any anesthesia and after the procedure the patient can return into his routine activity only with the minimal aid of NSAIDs. Two different types of hysteroscopes are used worldwide: flexible or rigid, which are made in different sizes. Optic miniaturization has been one of the greatest technological advancements in the field of hysteroscopy, both for rod-lens and fiberoptic scopes. The main concerns in office hysteroscopy are the need for necessary expertise, pain management and management of the complications in the office setting and the high cost of the equipment needed for the procedure. But office hysteroscopy has already demonstrated good correlation of findings compared with inpatient hysteroscopy, providing distinct advantages such as reduced anesthesia risks, enhanced time and cost-effectiveness, and faster recovery with less time away from work and home.